Intravascular extension of papillary thyroid carcinoma to the internal jugular vein: A case report - Al-Jarrah, Q. (Elsevier, 2014)
INTRODUCTION: Papillary thyroid cancer (PTC) is the most common thyroid malignancy and usually spreads via lymphatic system. PTC can sometimes show microscopic vascular invasion, but rarely causes tumour thrombus in the internal jugular vein (IJV) or other great veins of the neck. PRESENTATION OF CASE: We report a case of a 62-year-old female presented with symptomatic central neck mass. Clinical examination revealed a hard solitary right-sided thyroid nodule with ipsilateral cervical lymphadenopathy. Ultrasonography (US) confirmed the clinical diagnosis and visualised a dilated ipsilateral IJV. Fine-needle aspiration cytology revealed PTC cells so total thyroidectomy with right neck dissection was done. A tumour thrombus was discovered in the distended right IJV and was cleared successfully. The patient recovered well after the operation with no local or distant metastasis detected. DISCUSSION: Tumour vascular spread is observed in tumours with angio-invasive features including follicular carcinoma of the thyroid gland where great cervical veins can be affected. PTC commonly spreads to the lymph nodes and vascular spread via direct intravascular extension is extremely rare. Neck US has an important role in the diagnosis, and operators should attempt to detect signs of tumour thrombi in all patients with thyroid masses. Aggressive surgical treatment with vascular repair is recommended whenever possible to minimise the risk of potentially fatal complications of the intraluminal masses. CONCLUSION: Intravascular tumour extension of PTC is rare but with serious consequences. Diagnosis with neck US is possible but some cases are only discovered intraoperatively. Thrombectomy with vascular repair or reconstruction is usually possible.